Perceptions of Dental Students in Isfahan about Their Learning Environment, and Its Relationship with Academic Burnout - Fatemeh Shojaii; Hajar Shekarchizadeh; Simin Zahra Mohebbi (Isfahan University of Medical Sciences, 2023)
The quality ofthe learning environment affects students' learning, and specific characteristics of the learning environment affects medical students' burnout. The aim of this study was to determine dental students' viewpoints on the learning environment in dental schoolsand its relationship with academic burnout.Materials & Methods:In this cross-sectional study, we investigated undergraduate dental students from Isfahan University of Medical Sciences and Islamic Azad University of Isfahan applying a convenient sampling method in 2021. Data were collected through social networking platformssuch asWhatsApp and Telegram,using the"Burnout Clinical Subtype Questionnaire" andthe"Dental School Learning Environment Survey". Man-Whitney U test, Kruskal-Wallis test, Spearman correlation coefficient, and a linear regression model served for analysis (p value < 0.05).Results:Among 300 dental students with amean age of 24.25 ± 2.72, 54.7% were women. The mean score forthe dental school learning environment was 2.92 ± 0.30outof amaximum score of 5. The highest score was belonged to the dimension of organizing educational program (3.13 ± 0.45). The mean score of academic burnout was 2.61 ± 0.66 of the maximum score of 5. The highest score belonged to the dimension of overload (3.34 ± 0.87). A reverse association revealed between the dental school learning environment and academic burnout (r = -0.2, p value < 0.001).Conclusion:Dental students in Isfahan reported the quality of their dental school learning environment as well as their academic burnout as average. Regarding the reverse association betweenthelearning environment and academic burnout, it is suggested to plan interventions aimed atimprovingthe dental school learning environment and reducingthe academic burnout